Effects of consumption of Mauritia flexuosa fruits on renal and hepatic functions in growing rats - Romero, Amanda Batista da Rocha; Ferreira, Nayara Ravenna Trindade; Brito, Ana Karolinne da Silva; Cunha, Francisco Valmor Macedo; Lima, Simone Kelly Rodrigues; Lima, Alessandro de; Figueiredo, Francisco Cardoso; Lima, Sidney Gonçalo de; Rizzo, Márcia dos Santos; Nunes, Paulo Humberto Moreira; et al. (ABCS Health Sciences, 2023)
Introduction: Previous studies have reported that buriti (Mauritia flexuosa L. f.) is a typical fruit from the Brazilian cerrado ecosystem and an important food source for low-income populations. Its composition is rich in carotenoid polyphenols, monounsaturated fatty acids, and ascorbic acid. However, studies on the biological effects resulting from the consumption of this fruit are scarce. Objective: To evaluate the effects of a diet supplemented with buriti (Mauritia flexuosa L. f.) on kidney and liver functions in growing rats. Methods: Determination of centesimal composition, carotenoids, and fatty acids content for buriti pulp, standard chow, and butiti-supplemented chow were performed. Then, Wistar rats of both sexes were fed a standard diet or supplemented with buriti pulp. Blood samples were collected at the end of the experiment to determine biochemical parameters. The unpaired t-test was applied, and differences were considered significant when p<0.05. Results: A diet enriched with buriti pulp did not interfere with kidney function and most markers of liver function in animals. Alkaline phosphatase showed significantly higher plasma concentration in female rats, and albumin and uric acid showed lower concentrations in male rats in both experimental groups. Conclusion: The changes observed in biochemical markers did not provide evidence of adverse effects of buriti pulp supplementation on liver function. Thus, the intake of buriti pulp can be encouraged as it is a low-cost food source for the general population.